Covering District Heating Demand with Waste Heat from Data Centres: A Feasibility Study in Frankfurt, Germany - Jürgens, Bjarne; Zipplies, Johannes; Sauer, Christian; Kusyy, Oleg; Orozaliev, Janybek; Jordan, Ulrike; Vajen, Klaus (International Journal of Sustainable Energy Planning and Management, 2024)
Currently, the huge potential of data centre waste heat for the decarbonization of the heating sector is often ignored. Here, a feasibility study is presented for covering the heat demand of two districts of Frankfurt (Germany) mainly by data centre waste heat. Contrary to many existing projects, the waste heat shall supply existing buildings, the total heat demand is very high (144 GWh/a) and it should be covered almost exclusively by waste heat usage. In this study, the potential and demand are estimated, a heating supply concept is presented and evaluated regarding costs, heat pump capacity, and storage size. As a result, the utilisation of data centre waste heat is not only possible, but it’s the most promising way for decarbonizing the heating sector in this area. With high-capacity heat pumps (37 MWth), gas boilers (20 MWth) and a storage for daily peaks, 97.5 % of the heat demand can be covered by waste heat usage. It is economically favourable compared to decentralized heat pumps for all types of buildings and with the proposed concept, CO2-emissions in the network area are reduced by 78 % on average. Laws to oblige the waste heat usage of data centres are recommended.